The Role of Search Engine Optimization in Determining Journalism Quality - Sari Endah Nursyamsi; Nasaruddin Siregar; Nita Komala Dewi (Jurnal Ilmiah Teknik Informatika dan Komunikasi, 2023)
The SEO strategy for news content is characterized by employing mass media around an issue and then creating it frequently by writing as much as possible. Current event keywords are constantly incorporated into news content. Finally, the news will appear near the top of search engine results. Writing adapts to culture, particularly by observing text dynamics. Remember to evaluate editorial efforts in order to maintain journalistic quality. Data gathered through in-depth interviews, observations, and documentation. According to the findings of this study, all four media surveyed believe that SEO is a method of increasing traffic so that advertisements can develop. Doing SEO and then showing politically on the top page of Google search also puts other leading media's excellent reputation at danger. Publishers also develop regional content and implement target page view policies to ensure that the editorial staff adheres to the SEO algorithm. Surprisingly, there are limits on how SEO publishers may provide great information.